Physical Performance and Cross Layer Design for Wireless Mesh Networks - Muhammad, M.; Salleh, Mohd Shukor; Zakaria, M. S.; Gannapathy, Vigneswara Rao; Mohd Nor, Husain; Mohd Ibrahim, Imran; Muhammad Syahrir, Johal; Ahmad, Mohd Riduan; Abdul Aziz, Mohamad Zoinol Abidin (2008)
Wireless mesh networks (WMNs) are an alternative technology for last-mile broadband Internet access that can support broadband services. However, for a WMN to be all it can be, considerable research efforts are still needed. In WMNs, the Orthogonal Frequency Division Multiplexing (OFDM) system is chose to provide the better performance at the physical layer design. OFDM is very tolerant to ISI and it's spectrally efficient. OFDM also very susceptible to phase and frequency offsets. This paper presents the physical layer design of an OFDM system for wireless mesh networking